Revitalizing Universiti Sains Islam Malaysia (USIM) as a green space functions as a therapeutic landscape for the students / Siti NurNajah Sharin - Sharin, Siti NurNajah (2023)
In-depth knowledge of green areas as healthy campus environments will be provided through this study. The study will be in line with the area of focus where green space provides students with a healing atmosphere. Identity, sense of place, historical significance, and emotional responses to a therapeutic landscape are all taken into account by the symbolic space's appropriative dimension. The focus is on examining the processes by which the academic green space on campus is converted into a crucial health resource for numerous students. In this study, the augmentation of "direct attention" as a cognitive benefit that a campus with a holistic design can offer as a resource for learning was the main focus. Utilizing college campuses' full potential as attentional resources will require an understanding of their landscapes as essential learning environments.